Analisis Perbandingan Pendapatan Usahaternak Ayam Pedaging (Broiler) antara Peternak yang Bermitra dengan PT MSJ dan PT PKP - NI LUH TRISNA DIPA WAHYUNINGSIH; KETUT BUDI SUSRUSA; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
The Comparative Analysis of Broiler Farmer Income between Breeders Parthership with PT MSJ and PT PKP Poultry is one of the most livestock business which most of efficiently developed to support the community's economy. However, a lot of risks encountered in poultry. In reducing the risks of loss and to stabilizing income through a partnership between breeder and partner companies likes PT Mitra Sinar Jaya and PT Primatama Karya Persada. This research refers to breeder who partnership with PT Mitra Sinar Jaya and PT Primatama Karya Persada which aims to analyze the comparative of poultry’s income through grouping broilers population based on business scale. Population which grouped into a business scale are 2.000 – 5.000 chickens, 6.000 – 9.000 chickens and 10.000 – 13.000 chickens. For location determination was carried out using the census method on four breeders who partnership with PT Mitra Sinar Jaya and using the accidental sampling method on six breeders who partnership with PT Primatama Karya Persada. The result of this research indicate that income of business scale from 2.000 – 5.000 chickens in PT MSJ were Rp22.292.388/period and breeder from PT PKP were Rp20.885.480/period. On a bussines scale from 6.000 – 9.000 chickens income earned by breeder form PT MSJ were Rp38.232.413/period and breeder from PT PKP were Rp25.887.416/period. And then, income of business scale from 10.000 – 13.000 chicken from PT MSJ were Rp51.014.233/period and breeder from PT PKP were Rp71.309.400/period. The result of the Mann-Whitney statistically is insignificant.